2017
DOI: 10.1007/s10973-017-6126-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of differential scanning calorimetry to study porous structure of hydrothermally modified silicas

Abstract: The paper presents the studies on determination of physicochemical and structural properties of hydrothermally treated (HTT) silica gel Si-60, using the differential scanning calorimetry (DSC) and N 2 adsorption methods. Modification was performed in overheated water vapours or under the liquid water layer using various sources of thermal energy (in the classical autoclave or in the high-pressure microwave reactor). The characteristics of porous structure were determined on the basis of low-temperature nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Bühlmann reported that silica gel in contact with water vapor at increased temperatures of up to 200 °C (melt temperature in this study was up to 210 °C) caused decrease of surface area and increase of pore diameters (less smaller pores) in silica gel [103]. Hydrothermal changes of the silica gel structure, such as lower surface area and higher pore diameters already at 200 °C, were observed by Leboda et al and Charmas [104,105,106,107].…”
Section: Resultssupporting
confidence: 54%
“…Bühlmann reported that silica gel in contact with water vapor at increased temperatures of up to 200 °C (melt temperature in this study was up to 210 °C) caused decrease of surface area and increase of pore diameters (less smaller pores) in silica gel [103]. Hydrothermal changes of the silica gel structure, such as lower surface area and higher pore diameters already at 200 °C, were observed by Leboda et al and Charmas [104,105,106,107].…”
Section: Resultssupporting
confidence: 54%
“…The introduction of additives into the reaction mixture was made in different ways: in the sol stage at 20 • C in air (samples 1, 2, and 3), the sol-gel transition at 200 • C in the autoclave (HTT, samples 4, 5, 6, and 7), or in the wet gel stage during MChT at 300 rpm (samples 8,9,10) or 500 rpm (sample 11). MChT was performed using the ball mill Pulverisette-7 (Fritsch, Germany).…”
Section: Preparationmentioning
confidence: 99%
“…The differential f S (R) functions were used to estimate the deviation (∆w) of the pore shape [21]. The f V (R) functions were also used to calculate the contribution of micropores (V micro , S micro for R p < 1 nm), mesopores (V meso , S meso for 1 nm < R p < 25 nm), and macropores (V macro , S macro for R p > 25 nm) [10,22,23]. The obtained results are summarized in Table 1.…”
Section: Textural Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations